Analisis Lingkungan Organisasi Pencak Silat Persaudaraan Setia Hati Terate (PSHT) Dalam Melatih Rasa Persaudaraan dan Bersosialisasi Pada Sesama Siswa dan Warga PSHT Rayon Dukuh Tengah - Muhammad Alim Syafiqin; Wahyu Eko Pujianto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Pencak Silat Persaudaraan Setia Hati Terate (PSHT) is a pencak silat organization that has a long and rich history in Indonesia. Founded in 1922, PSHT has developed into an international organization with members around the world, including in Rayon Dukuh Tengah. This study aims to describe the teachings of PSHT on the values of socializing character education in the community (Study on students of Silat PSHT Rayon Dukuh Tengah Ranting Buduran Sidoarjo Branch). This research uses qualitative methods with interviews. The results of this study indicate that the values of the implementation of socializing character education in students are that students behave with courtesy when interacting with other people, students are willing to listen when given advice by others, students are tolerant of differences with PSHT members and other organizational groups, students want to be involved in community activities.